ANALISIS CONJECTURING MAHASISWA UIN SATU TULUNGAGUNG DALAM PEMECAHAN MASALAH MATEMATIKA - Sutopo, Sutopo; Diniati, Bintis Ti’anatud (Universitas Bhinneka PGRI, 2024)
This study examines the role of mathematical conjecturing in problem-solving by students at UIN SATU Tulungagung, as many students still have conjectures that do not align with the correct solution concepts. The aim of this study is to describe the process of conjecturing among students in solving mathematical problems. This research is qualitative, with the researcher acting as the main instrument to reveal the process behind the problem-solving outcomes. The subjects of the study are sixth-semester students of the Mathematics Education program who have taken courses in algebra, geometry, trigonometry, and calculus. The findings indicate that the students' conjecturing abilities are quite good, including their ability to test data, propose mathematical models, formulate conjectures, and test conjectures using formal proofs.